Plants causing poisoning outbreaks of livestock in South America: A review - Riet-Correa, Franklin; Machado, Mizael; Micheloud, Juan Francisco (Elsevier, 2023)
According to Tokarnia et al. (2012), “poisonous plants of livestock interest are those that, when ingested by farm animals under natural conditions, cause health problems or death.” Following this definition, we include in this manuscript only toxic plants that have been proven to cause at least one outbreak of spontaneous poisoning in livestock in South America. In most of these plants, the toxicity was demonstrated by observing outbreaks and by the experimental reproduction of the disease. Also, we include as toxic plants for livestock those that contain a known toxic compound causing outbreaks of disease typical of this compound (e.g., fluoroacetate, nitrites, cyanogenic glycosides, pyrrolizidine alkaloids, swainsonine), and the diagnostic was based on clinical signs, pathology, and determination of the toxic compound in the plant. In this manuscript, we did not consider as toxic plants many species that occur in South America and have been reported as toxic in other regions, sometimes with a known toxic compound, but outbreaks in South America have not been demonstrated and published (e.g., Taxus baccata, Datura stramonium, Nicotiana glauca, and Asclepias curassavica). We also did not include those plants whose toxicity has been experimentally demonstrated in South America, but no spontaneous outbreaks of intoxication have been recorded.